Filosofi Dan Matematika Motif Batik Sindu Melati: Studi Etnografi Pembelajaran Kontekstual - Hidayati, Miftachul; Windi Hastuti; Sukimin; Naufal Ishartono (Pendidikan Matematika Universitas PGRI Yogyakarta, 2025)
Batik is a traditional Indonesian craft that involves the technique of dyeing cloth using wax to create beautiful motifs with certain patterns. This study explores the ethnomathematics of the Batik Sindu Melati motif, because there are many ethnomathematic studies on batik, but none have studied it. This study explores the philosophy of instilling unique cultural insights as a form of conservation of Indonesian culture and the mathematical concepts contained therein. The purpose of the study is to describe the philosophy and mathematical concepts of Batik Sindu Melati. This qualitative ethnographic research, with a research method, answers four ethnographic research questions that must be answered by researchers. Data collection through observation, semi-structured interviews with craftsmen and mathematicians, and documentation. The results of the study, Batik Sindu Melati, contain geometric concepts such as geometric transformation, plane geometry, symmetry, similar and congruent, and arithmetic concepts in the form of ratios. This study concludes that the Sindu Melati Batik motif contains mathematical concepts that can be utilized in learning, especially with an ethnomathematics approach, and is expected to be used for the development of contextual and meaningful mathematics teaching materials, as well as being an effort to conserve the Sindu Melati Batik culture. Keywords: Batik Sindu Melati, Ethnography, Ethnomathematics